2012
DOI: 10.1021/tx200513t
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Caused by Metal Nanoparticles: Involvement of Oxidative Stress and Activation of ATM

Abstract: Nanotechnology is a fast growing emerging field, the benefits of which are widely publicized. Our current knowledge of the health effects of metal nanoparticles such as nano-sized cobalt (Nano-Co) and titanium dioxide (Nano-TiO2) is limited but suggests that metal nanoparticles may exert more adverse pulmonary effects as compared with standard-sized particles. To investigate metal nanoparticle-induced genotoxic effects and the potential underlying mechanisms, human lung epithelial cell lines A549 cells were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 45 publications
(154 reference statements)
12
93
0
2
Order By: Relevance
“…In contrast, exposures to ENPs may cause upregulation of the p53 tumor suppressor gene and to DNA repair proteins. Wan et al (2012) showed that ENPs can induce DNA damage and cell death via up-regulation of phosphorylated p53, histone H2AX (γ-H2AX) and via an ataxia telangiectasia mutant (ATM).…”
Section: Interaction With Proteinsmentioning
confidence: 99%
“…In contrast, exposures to ENPs may cause upregulation of the p53 tumor suppressor gene and to DNA repair proteins. Wan et al (2012) showed that ENPs can induce DNA damage and cell death via up-regulation of phosphorylated p53, histone H2AX (γ-H2AX) and via an ataxia telangiectasia mutant (ATM).…”
Section: Interaction With Proteinsmentioning
confidence: 99%
“…21 The generation of free radicals is known to cause oxidative damages in DNA and subsequently produce the product 8-hydroxy-2′-deoxyguanosine , an established oxidative DNA damage marker. 22 An in vitro study demonstrated that ZnO NPs (#35 or 50-80 nm) are able to cause oxidative DNA damage and genotoxicity as revealed by the Comet assay in human lymphoblastoid cells. 23 Other studies using mammalian cultured cells have also shown the potential risk of ZnO NPs in the induction of genotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…14 The cytotoxicity of cobalt (Co) and CuO NPs to human lung epithelial A549 cells were reported recently. 15,16 Both of these studies concluded that reactive Plants, as an essential component in the environment, are critical to ecosystem function and food supply integrity. Based on the findings of recent laboratory studies, abiotic and oxidative stresses caused by NPs exposure in plants were described at both physiological and biochemical levels.…”
Section: Introductionmentioning
confidence: 99%